Annual Plan Progress Report (1966-67 To 1968-69) Government of Haryana - Planning Commission (Planning Commission, 1966)
Development and Economic growth through Planning.—The process of planned economic development was adopted by the country nearly two decades ago with the object of increasing productivity, raising living standard and opening new opportunities for richer and more varied life. The specific aim was to double the per capita income by 1977-78 or roughly within a span of a generation. With this broad perspective, each successive Five-Year Plan had a distinct role to Play. The First Five Year Plan sought to rehabilitate the economy from the ravages of war, famine and partition and to build up institutions which would help the economy to develop in the desired direction. The Second Five-Year Plan was designed to carry the process further, accelerate the rate of growth which would initiate a strategy to assist and bring about structural changes in economy for achieving the long term objective of development. There was a special emphasis for the maximisation of rate of capital formation.
Government of Haryana, Economic and Statistical Organisation, Planning Department